PENGARUH METODE DRILL BERBANTUAN SOAL ANIMASI TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF SISWA PADA KONSEP DINAMIKA PARTIKEL - Shinta Fitriyani; Erina Hertanti; Ai Nurlaela (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
This research aims to prove the effect of drill method by questions format with animation to reflective thinking skills students on the dynamic particle concept. The research was conducted on February 2016 in SMA Negeri 1 Karawang. This research has two samples, there were X MIPA 1 as control class and X MIPA 6 as experiment class. The research method was a quasi experiment with nonequivalent control group design and the sampling technique was purposive sampling. The instrument divided into two types, test with essay questions and non-test with the questionnaire. A hypothesis based on testing that used t-test to post test result the value of tcount was 2.00 and table was 1,99, that showed the value of tcount>ttable, so H0 was rejected. It means, the drill method by questions format in the form of animation was proved the influence of reflective thinking skills students. Kata-kata Kunci: Metode Drill, Soal dalam format Animasi, Kemampuan Berpikir Reflektif